Theoretical prediction of hysteretic rubber friction in ball on plate configuration by finite element method (eXPRESS Polymer Letters, 2009)
This paper has investigated theoretically the influence of sliding speed and temperature on the hysteretic friction in case of a smooth, reciprocating steel ball sliding on smooth rubber plate by finite element method (FEM). Generalized Maxwell-models combined with Mooney-Rivlin model have been used to describe the material behaviour of the ethylenepropylene-diene-monomer (EPDM) rubber studied. Additionally, the effect of the technique applied at the parameter identification of the material model and the number of Maxwell elements on the coefficient of friction (COF) was also investigated. Finally, the open parameter of the Greenwood-Tabor analytical model has been determined from a fit to the FE results. By fitting, as usual, the Maxwell-model to the storage modulus master curve the predicted COF, in a broad frequency range, will be underestimated even in case of 40-term Maxwell-model. To obtain more accurate numerical prediction or to provide an upper limit for the hysteretic friction, in the interesting frequency range, the Maxwell parameters should be determined, as proposed, from a fit to the measured loss factor master curve. This conclusion can be generalized for all the FE simulations where the hysteresis plays an important role.